Pollen Aquaporins: The Solute Factor - Pérez Di Giorgio, Juliana A.; Soto, Gabriela C.; Muschietti, Jorge P.; Amodeo, Gabriela (Frontiers in Plant Science, 2016)
In the recent years, the biophysical properties and presumed physiological role of aquaporins (AQPs) have been expanded to specialized cells where water and solute exchange are crucial traits. Complex but unique processes such as stomatal movement or pollen hydration and germination have been addressed not only by identifying the specific AQP involved but also by studying how these proteins integrate and coordinate cellular activities and functions. In this review, we referred specifically to pollen-specific AQPs and analyzed what has been assumed in terms of transport properties and what has been found in terms of their physiological role. Unlike that in many other cells, the AQP machinery in mature pollen lacks plasma membrane intrinsic proteins, which are extensively studied for their high water capacity exchange. Instead, a variety of TIPs and NIPs are expressed in pollen. These findings have altered the initial understanding of AQPs and water exchange to consider specific and diverse solutes that might be critical to sustaining pollen’s success. The spatial and temporal distribution of the pollen AQPs also reflects a regulatory mechanism that allowing a properly adjusting water and solute exchange.